Group 2 Innate Lymphoid Cells in Allergic Rhinitis - Wang S; Liu X; Lin X; Lv X; Zhang H (Dove Medical Press, 2024)
Shuang Wang,1- 4,* Xuexia Liu,5 Xinhua Lin,1- 4,* Xiaojing Lv,2- 4 Hua Zhang2- 4 1School of Clinical Medicine, Shandong Second Medical University, Weifang, People's Republic of China; 2Department of Otorhinolaryngology, Head and Neck Surgery, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China; 3Shandong Provincial Clinical Research Center for Otorhinolaryngologic Diseases, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China; 4Yantai Key Laboratory of Otorhinolaryngologic Diseases, Yantai Yuhuangding Hospital, Qingdao University, Yantai, People's Republic of China; 5Shandong Stem Cell Engineering Technology Research Center, Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, People's Republic of China*These authors contributed equally to this workCorrespondence: Xuexia Liu; Hua Zhang, Department of Otorhinolaryngology & Head and Neck Surgery, Yuhuangding Hospital Affiliated to Qingdao University, No. 20 East, Yuhuangding Road, Yantai, Shandong, 264000, People's Republic of China, Tel +86-15154502782, Email xue6er6@163.com; zhang0hua@163.comAbstract: Allergic rhinitis (AR), which presents symptoms like sneezing and a runny nose, is categorized as an upper respiratory condition of type 2. Recent progress in comprehending AR has revealed the significant role played by type 2 cytokines, specifically interleukin (IL)-13, IL-4, and IL-5. These cytokines are released by helper T cells 2 (Th2) and innate lymphoid cells (ILC2s). ILC2s have the ability to interact with various immune cells and are essential in promoting both type 2 immune response and tissue repair, contributing to normal homeostatic functions within the body. This article presents a summary of the latest advancements in comprehending the activity of ILC2s, with particular emphasis on their potential role involvement in AR. It explores how they collaborate with Th2 cells to exacerbate nasal inflammation and interact with regulatory T cells (Tregs) to counteract the suppressive role mediated by Tregs during allergic inflammation. The significance of ILC2s in allergen-specific therapy is highlighted. A comprehensive understanding of ILC2s biology establishes a robust foundation for unraveling the pathogenesis of AR and devising innovative therapeutic approaches for its management.Keywords: allergic rhinitis, group 2 innate lymphoid cells, cytokines, Treg cells, Th2 cells